2003
DOI: 10.1002/ijc.11019
|View full text |Cite
|
Sign up to set email alerts
|

Mutation analysis of DMBT1 in glioblastoma, medulloblastoma and oligodendroglial tumors

Abstract: DMBT1 has been implicated as a candidate tumor suppressor gene on chromosome 10q for brain, gastrointestinal and lung cancer. Homozygous deletion and lack of expression are 2 known mechanisms for inactivating DMBT1. We evaluated whether somatic mutation, which represents a major inactivation mechanism for most tumor suppressor genes, occurs in the DMBT1 gene. A total of 102 primary brain tumors, consisting of 25 glioblastoma multiforme, 24 medulloblastoma and 53 oligodendroglial tumors, were analyzed by confor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 21 publications
0
16
1
Order By: Relevance
“…There is a large body of literature supporting an association of DMBT1 with cancer (2,5,23,26,35,37). However, other studies have failed to provide a link between DMBT1 and cancer (20,40,41). We did not find evidence that a lack of Muclin caused gastrointestinal tumors.…”
Section: Discussioncontrasting
confidence: 75%
“…There is a large body of literature supporting an association of DMBT1 with cancer (2,5,23,26,35,37). However, other studies have failed to provide a link between DMBT1 and cancer (20,40,41). We did not find evidence that a lack of Muclin caused gastrointestinal tumors.…”
Section: Discussioncontrasting
confidence: 75%
“…Consistent with our finding, both the mRNA and protein levels of DMBT1 were determined to be lower in CSCC tissues than that in the adjacent normal tissues after examination of qRT‐PCR and Western blot methods, demonstrating a tumor suppressor role in CSCC. Notably, the downregulation of DMBT1 in many tumor cell lines and primary tumors has been reported to be possibly associated with allele loss, homozygous deletion, base substitution, structural rearrangement, or promoter methylation according to the previous studies, but its detailed mechanism of DMBT1 downexpression in CSCC has not been clarified, which would explore in our future research.…”
Section: Discussionmentioning
confidence: 88%
“…In agreement with this, we observed that the abundance of decorin significantly decreases at the angiogenic switch and is even further decreased in advanced insulinoma. Dmbt1 has been shown to be deleted or mutated in various tumor types41424344. Future work will be required to evaluate whether hemicentin or Vwa5a play functional roles in cancer progression and the angiogenic switch.…”
Section: Resultsmentioning
confidence: 99%